Voltage sag acceptability assessment using multiple magnitude-duration function - Tan R.H.G.; Ramachandaramurthy V.K. (2023)
A multiple magnitude-duration (MMD) function is proposed for voltage sag acceptability assessment. The MMD function is a statistical representation of voltage sag derived from its rms analysis. The MMD function maps a series of correlated sag magnitude and duration points onto the standard power acceptability curve, revealing the dynamic characteristic of voltage sag across the standard power acceptability curve. It allows nonrectangular voltage sag, such as voltage sag due to transformer energization, induction motor starting, multistage fault, self-extinguishing fault, and voltage sag influenced by induction load to be assessed. The practicality and advantage of the proposed MMD acceptability assessment is evaluated using practical data and IEEE1159.2 waveforms set on an ITIC and SEMI F47 standard power acceptability curve. The evaluation results show that the proposed MMD function yields higher resolution and improved acceptability assessment accuracy compared to the conventional single-point mapping assessment. 1986-2012 IEEE.